Exchange rate effects on international commercial trade competitiveness - Ionel Bostan; Carmen Toderașcu Sandu; Bogdan-Narcis Firtescu (Journal of Risk and Financial Management, 2018)
This study is meant to be an evaluation sustained by theoretical and empirical considerations of the exchange rate impact on international commercial trade competitiveness. In this respect, the study aims to find how the exchange rate influences Romanian competitiveness through assessing the effects generated on exports and imports. The main purpose of the study is to assess the complex action of the exchange rate on international commercial trade competitiveness in contemporaneity and the connections between these variables. The empirical part contains a regression analysis where exports and imports are dependent variables influenced by a series of determinants.
Keywords: 330; exchange rate; economic competitiveness; exports; imports; multiple regression